Analysis XYZ School Digital Marketing Performance With Importance Performance Analysis - Esti Rahayu; Yudha Heryawan Asnawi; Denny Bernadus Kurnia (Business Review and Case Studies, 2024)
Background: XYZ School implements digital marketing to accept new students. Purpose: This research aims to analyze digital marketing performance so that it can identify priorities for improving digital marketing performance. Design/methodology/approach: The research method was quantitative, using descriptive analysis through surveys conducted with the new student admissions team and the XYZ school digital marketing team. The study was carried out using Importance Performance Analysis (IPA) with the Digital Marketing Utilization Index indicator.Findings/results: The main priority for improving the digital marketing performance of XYZ School was that school management needed to actively introduce innovation and readiness for XYZ School by clarifying the digital marketing workflow to provide convenience in the process of accepting new students.Conclusion: This research found that efforts to improve digital marketing performance in K-12 educational institutions could be made by actively introducing school management to innovation and preparing to implement digital marketing strategies. This approach would enable the New Student Admissions team to easily apply digital marketing innovations, utilize digital marketing for building interactions between the school and parents and students, and facilitate the registration process for prospective students by providing a website with comprehensive information about the school.Originality/value (State of the art): This research contributes to K-12 education institutions in improving digital marketing performance in efforts to accept new students and maintain customer loyalty to maintain school sustainability. Keywords: digital marketing, Importance Performance Analysis, K12 educational institution, new student admission, school